Pembelajaran Berbasis Audio Visual pada Materi Teks Laporan Hasil Observasi Kelas X SMA Budi Agung Medan - Hasibuan, Siti Oriza Satipa; Safina, Nila; Amaluddin, Amaluddin (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study examines Indonesian language learning in class X SMA Budi Agung Medan, focusing on the development of audiovisual-based learning media using Macromedia Flash software. The 2013 curriculum necessitates adaptable learning media to facilitate students' independent learning with teachers as facilitators. However, the current text-based learning approach is limited. The research used the research and development (R&D) method with the ADDIE development model. Data were collected from media and material experts, as well as lecturers and teachers in Indonesian language studies and learning media. The results showed that the audiovisual-based learning media received a feasibility value of 84.0% (appropriate) for media and 81.0% (adequate) for material. The teacher's response to the media was 80.76%, while the student's response was 80.2%. This study highlights the importance of implementing effective learning media in line with the 2013 curriculum to enhance the learning experience.